2016
DOI: 10.15376/biores.11.4.9095-9111
|View full text |Cite
|
Sign up to set email alerts
|

Milling of Heat-Treated Beech Wood (Fagus sylvatica L.) and Analysis of Surface Quality

Abstract: Several previous studies have investigated the effects of heat treatment on the chemical composition, along with the physical and mechanical properties, of wood from various species. However, the effects of these property changes upon the machining properties and surface quality of machined wood have been studied much less. The main goal of this work was to investigate the comparative cutting power consumption during milling and the resulting surface roughness of heat-treated and untreated beech wood (Fagus sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 17 publications
5
21
0
Order By: Relevance
“…Findings of the experiments by Škaljić et al (2009) revealed that roughness Ra of thermally modifi ed beech-wood was very close to the same values of steamed beech-wood samples. However, the surface roughness of heat-treated beech processed by milling was slightly higher than that of untreated wood (as measured by Ra, Rq, Rt, Rk, and Rk+Rpk+Rvk) (Ispas et al, 2016). The latter fi ndings were confi rmed by Hacibektasoglu et al (2017), who revealed that heattreating beech (Fagus sylvatica L.) for 1 h and 2 h had a negligible effect on the processing roughness after planning, measured across the grain by Rk.…”
Section: Introduction 1 Uvodmentioning
confidence: 73%
“…Findings of the experiments by Škaljić et al (2009) revealed that roughness Ra of thermally modifi ed beech-wood was very close to the same values of steamed beech-wood samples. However, the surface roughness of heat-treated beech processed by milling was slightly higher than that of untreated wood (as measured by Ra, Rq, Rt, Rk, and Rk+Rpk+Rvk) (Ispas et al, 2016). The latter fi ndings were confi rmed by Hacibektasoglu et al (2017), who revealed that heattreating beech (Fagus sylvatica L.) for 1 h and 2 h had a negligible effect on the processing roughness after planning, measured across the grain by Rk.…”
Section: Introduction 1 Uvodmentioning
confidence: 73%
“…The data used in this study were taken from Ispas et al (2016). Namely, the present study does not conduct the experiments for determining the influences of treatment, rotation speed, cutting depth, and feed rate on power consumption in the wood milling process.…”
Section: Methodsmentioning
confidence: 99%
“…Namely, the present study does not conduct the experiments for determining the influences of treatment, rotation speed, cutting depth, and feed rate on power consumption in the wood milling process. Instead, it aims at predicting the influences of the aforementioned variables on power consumption using the data obtained from the experimental results of Ispas et al (2016). Some experimental details were explained below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations